MANFAAT GADGET SEBAGAI SUMBER BELAJAR ONLINE SISWA SD DI MASA PANDEMI COVID-19 - Erika Erika; Siti Mayang Sari; Yamnur Nurmalia (Universitas Negeri Medan, 2021)
Abstract: Benefits of Gadgets as An Online Learning Resource for Elementary Students In The Covid-19 Pandemic. Gadgets as online learning resources are used effectively, efficiently and beneficially for elementary school students. Excessive use of gadgets has a negative impact on the development of elementary school students. This study aims to describe how the use of gadgets as an online learning resource for elementary school students. Currently one of the learning tools for elementary school students is a gadget because learning is used online, this is done to break the chain of the spread of COVID-19. This research method uses literature study or literature review. The steps in the literature review are finding the topic, determining the title, and making conclusions. From the results of the journal literature, it shows that elementary school students can use gadgets as online learning resources through the supervision of parents and teachers. Because of the impact of using everyday gadgets in the online learning process, elementary school students usually only play games, watch animated films, and so on. This literature study describes the need for parental supervision for elementary school students' learning activities in using gadgets during online learning. Keywords: Gadgets, Learning Resources, Online Abstrak: Manfaat Gadget Sebagai Sumber Belajar Online Siswa Sd Di Masa Pandemi Covid-19. Gadget sebagai sumber belajar online digunakan secara efektif, efisien dan bermanfaat bagi siswa sekolah dasar. Pemanfaatan gadget yang berlebihan berdampak buruk bagi perkembangan siswa sekolah dasar. Penelitian ini bertujuan untuk mendeskripsikan bagaimana pemanfaatan gadget sebagai sumber belajar online bagi siswa sekolah dasar. Saat ini salah satu alat belajar siswa sekolah dasar adalah gadget karena pembelajaran digunakan secara online, hal ini dilakukan guna memutus rantai penyebaran covid-19. Metode penelitian ini menggunakan studi literatur atau literatur review. Langkah dalam kajian literatur adalah pencarian topik, menentukan judul, dan penyimpulan. Dari hasil literatur jurnal, menunjukkan siswa sekolah dasar dapat memanfaatkan gadget sebagai sumber belajar online melalui pengawasan orang tua dan guru. Karena dampak pemanfaatkan gadget sehari-hari dalam proses pembelajaran online siswa sekolah dasar biasanya hanya untuk bermain game, menonton film animasi, dan lain-lain. Studi literatur ini mendeskripsikan perlunya pengawasan dari orang tua untuk kegiatan belajar siswa SD dalam memanfaatkan gadget selama pembelajaran online. Kata Kunci : Gadget, Sumber Belajar, Online